Triggers for acute flare in adults with, or at risk of, knee osteoarthritis: a web-based case-crossover study in community-dwelling adults. Issue 7 (July 2021) - Thomas, M.J.; Rathod-Mistry, T.; Parry, E.L.; Pope, C.; Neogi, T.; Peat, G.
Summary: Objective: To identify proximate causes ('triggers') of flares in adults with, or at risk of, knee osteoarthritis (OA), estimate their course and consequences, and determine higher risk individuals. Methods: In this 13-week web-based case-crossover study adults aged ≥40 years, with or without a recorded diagnosis of knee OA, and no inflammatory arthropathy who self-reported a knee flare completed a questionnaire capturing information on exposure to 21 putative activity-related, psychosocial and environmental triggers (hazard period, ≤72 h prior). Comparisons were made with identical exposure measurements at four 4-weekly scheduled time points (non-flare control period) using conditional logistic regression. Flare was defined as a sudden onset of worsening signs and symptoms, sustained for ≥24 h. Flare characteristics, course and consequence were analysed descriptively. Associations between flare frequency and baseline characteristics were estimated using Poisson regression. Results: Of 744 recruited participants (mean age [SD] 62.1 [10.2] years; 61% female), 376 reported 568 flares (hazards) and provided 867 valid control period measurements. Thirteen exposures (eight activity-related, five psychosocial/environmental) were positively associated with flare onset within 24 h (strongest odds ratio estimate, knee buckling: 9.06: 95% confidence interval [CI] 5.86, 13.99; weakest, cold/damp weather: 1.45: 95%CI 1.12, 1.87). Median flare duration was 5 days (IQR 3, 8), less common if older (incident rate ratio [IRR] 0.98: 95%CI 0.97, 0.99), more common if female (IRR 1.85: 95%CI 1.43, 2.39). Conclusions: Multiple activity-related, psychosocial and environmental exposures are implicated in triggering flares. This evidence can help inform prevention and acute symptom management for patients and clinicians.